Woman Sensual Dance di Social Media Tiktok dalam Relasinya dengan Stigmatisasi Perempuan dan Imitative Culture - Irnawati Rosidah; Nur Afifah Afif; Moh Nadzir; Mukhid Masyhuri; Putri Nur Laila; Zainul Ahwan (IAI Darussalam, 2021)
This study aims to reveal how stigmatization and imitative culture occur in women caused by social media, especially TikTok in terms of Sara Mills' Discourse Analysis Theory. This research is a qualitative descriptive study. The subject of this research is the text, images and comments of netizens in the video woman sensual dance on the tiktok account. The results of this research indicate that the elements of Sara Mills' critical discourse analysis on the position of female stigmatized subjects occur from the content of woman sensual dance which emphasizes attractiveness through fashion styles, facial expressions, and dancing characters so that it raises negative views for women, from the writer's position. The reader is generated by conditions in the sensual dance content as shown in the Tiktok video showing that the current representation of women is indeed true, according to what has been stated in the netizen's comment text, namely having a bad image and an imitative culture that occurs from the many similar accounts that follow the trend.